Therapeutic roles of platelet-rich plasma to restore female reproductive and endocrine dysfunction - Wang, Xiaoning; Li, Jin; Lu, Weiwei; Gao, Fangbo; Zhang, Songling; Li, Jiajia (Frontiers in Endocrinology, 2024)
Millions of women worldwide are infertile due to gynecological disorders, including premature ovarian insufficiency, polycystic ovary syndrome, Asherman syndrome, endometrial atrophy, and fallopian tube obstruction. These conditions frequently lead to infertility and have a substantial impact on the quality of life of the affected couples, primarily because of their psychological implications and high financial costs. Recently, using platelets to stimulate cell proliferation and tissue differentiation has emerged as a promising approach in regenerative medicine. Platelet-rich plasma (PRP) shows considerable potential for promoting endometrial hypertrophy and follicle development, making it a promising therapeutic option for tissue repair or replacement. This review provides an overview of the recent advancements and underlying mechanisms of PRP therapy for various female reproductive diseases and presents new therapeutic options for addressing female infertility.